1993
DOI: 10.1177/000348949310200510
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Parotid Duct Fistula

Abstract: Parotid duct fistulas (PDFs) are rare and have various causes such as gunshot wounds and human and animal bites; they may also be congenital. We have not found previous publications on bilateral PDF. Our patient, although young, also had generalized pigmentation characteristic of aging and thick, dry, wrinkled skin, as well as pyoderma. Biochemical analysis was performed on discharge from the patient's face, and histopathologic and immunologic studies were done. The fistulas were treated by intraoral fistuliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Most of the authors who have treated this condition before used the following surgical technique: The aberrant duct was dissected, attached with a small skin island, and transposed into the oral cavity to redirect the fistula outflow. 3,4,5,7 The same technique may eventually be used to treat acquired parotid duct fistulas, as reported by Kabakkaya et al 8 Only 1 of the 7 previously reported cases of congenital accessory parotid fistula was treated by fistulectomy plus accessory parotid gland resection. 6 However, the procedure used by the previous authors was not well described; moreover, their procedure seemed to confer no advantage over the "standard" fistula intraoral translocation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Most of the authors who have treated this condition before used the following surgical technique: The aberrant duct was dissected, attached with a small skin island, and transposed into the oral cavity to redirect the fistula outflow. 3,4,5,7 The same technique may eventually be used to treat acquired parotid duct fistulas, as reported by Kabakkaya et al 8 Only 1 of the 7 previously reported cases of congenital accessory parotid fistula was treated by fistulectomy plus accessory parotid gland resection. 6 However, the procedure used by the previous authors was not well described; moreover, their procedure seemed to confer no advantage over the "standard" fistula intraoral translocation.…”
Section: Discussionmentioning
confidence: 90%
“…[4][5][6] After fusion of the maxillary and mandibular processes, which are both derived from the first branchial arch, the parotid duct takes its normal position inside the mouth at the level of the superior second molar. 4,7,8 An accessory parotid gland is a rather common anatomic variation that develops from the same embryologic origin as the main parotid gland. 2,3,5,6 It is normally located in front of the main gland in close proximity to the Stensen duct.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, studies on parotid duct surgery are very few. Kitamura and Togawa 4 and Kabakkaya et al 5 discussed the creation of a fistula to the oral cavity. The tendency of such a fistula to close, although created wide, was demonstrated in the outcome of the first operation on our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Die Mündungen der Fisteln wurden überwiegend im Bereiche der Wangenhaut beobachtet [7], gelegentlich sogar doppelseitig [5].…”
Section: Diskussionunclassified